Properties of modified sand brick using coconut shell - Abdul Hasib Mahamod (School of Environmental Engineering, University Malaysia Perlis, 2012)
In accordance with conservation efforts, this research focuses on prevention of environmental pollution and considers the elements of sustainable and cost-saving construction projects, especially material usage. The development of a new innovative, low cost building material that is composed of coconut shell waste where is widely available and extremely cheap resource, modified sand brick using coconut shell was investigated in this research. The main aim of this research is to identify the chemical composition of coconut shell and compare with chemical composition of cement to know whether it can react as a good binder in the mix. The physical properties of this modified sand brick including colours, texture, and density will be studied. Engineering properties such as 7 and 28 days compressive strength and water absorption shall be determined. After that, both properties of the modified sand brick are compared with the standard sand brick in the market. The specimen of the brick prepared in this research is standard brick named as BS, 10 %, 20 % and 30 % proportion of coconut shell known as B10, B20, B30 are used as part of cement replacement in the mixes. The ratio of the sand brick use in this research is 1:3 which stands for 1 part cement, 3 parts of sand. The findings withdrawn from this research are: first, the chemical composition of the coconut shell is almost similar to the chemical composition of cement. Second, the physical properties of modified sand brick are not too different from the standard brick, especially in terms of density. The addition of coconut shell reduces the compressive strength of bricks, and the maximum compressive strength obtained in this study is from specimen B10. Finally, the results showed a small decrease in water absorption in water absorption with increase in shell content in modified sand brick.